Repeat liver resection for recurrent colorectal metastases: a single‐centre, 13‐year experience. Issue 2 (27th March 2013) - Battula, Narendra; Tsapralis, Dimitrios; Mayer, David; Isaac, John; Muiesan, Paolo; Sutcliffe, Robert P.; Bramhall, Simon; Mirza, Darius; Marudanayagam, Ravi
Abstract Objectives Isolated intrahepatic recurrence is noted in up to 40% of patients following curative liver resection for colorectal liver metastases (CLM). The aims of this study were to analyse the outcomes of repeat hepatectomy for recurrent CLM and to identify factors predicting survival. Methods Data for all liver resections for CLM carried out at one centre between 1998 and 2011 were analysed. Results A total of 1027 liver resections were performed for CLM. Of these, 58 were repeat liver resections performed in 53 patients. Median time intervals were 10.5 months between the primary resection and first hepatectomy, and 15.4 months between the first and repeat hepatectomies. The median tumour size was 3.0 cm and the median number of tumours was one. Six patients had a positive margin (R1) resection following first hepatectomy. There were no perioperative deaths. Significant complications included transient liver dysfunction in one and bile leak in two patients. Rates of 1‐, 3‐ and 5‐year overall survival following repeat liver resection were 85%, 61% and 52%, respectively, at a median follow‐up of 23 months. R1 resection at first hepatectomy (P = 0.002), a shorter time interval between the first and second hepatectomies (P = 0.02) and the presence of extrahepatic disease (P = 0.02) were associated with significantly worse overall survival. Conclusions Repeat resection of CLM is safe and can achieve longterm survival in carefully selected patients. A preoperative knowledge of poor prognostic factors helps to facilitate better patient selection.